An electrostatic deflector for a fusion reaction - 张焕乔 林承键 杨峰 贾会明 周平 安广朋 张春雷 徐新星 (Chinese physics C, 2010)
An electrostatic deflector for separating the fusion evaporation residues from the beam-like products in heavy ion reactions was installed. The evaporation residue separation and identification with the electrostatic deflector setup was tested with the reaction ^32S＋^96Zr at several energies. The fusion evaporation residues and the beam-like particles were well separated after the electrical separation and the experimental fusion cross section obtained from the angular distribution is in good agreement with the calculated value well above the Coulomb barrier. This confirms the reliability of the setup.